Hierarchical 3D mesoporous silicon@graphene nanoarchitectures for lithium ion batteries with superior performance - Chen, Shuangqiang; Bao, Peite; Huang, Xiaodan; Sun, Bing; Wang, Guoxiu (Nano research, 2014)
Silicon has been recognized as the most promising anode material for high capacity lithium ion batteries. However, large volume variations during charge and discharge result in pulverization of Si electrodes and fast capacity loss on cycling. This drawback of Si electrodes can be overcome by combination with well-organized graphene foam. In this work, hierarchical three-dimensional carbon-coated mesoporous Si nanospheres@graphene foam （C@Si@GF） nanoarchitectures were successfully synthesized by a thermal bubble ejection assisted chemical-vapor-deposition and magnesiothermic reduction method. The morphology and structure of the as-prepared nanocomposites were characterized by field emission scanning electron microscopy, transmission electron microscopy and Raman spectroscopy. When employed as anode materials in lithium ion batteries, C@Si@GF nanocomposites exhibited superior electrochemical per- formance including a high specific capacity of 1,200 mAh/g at the current density of 1A/g, excellent high rate capabilities and an outstanding cyclability. Post-mortem analyses identified that the morphology of 3D C@Si@GF electrodes after 200 cycles was well maintained. The synergistic effects arising from the combination of mesoporous Si nanospheres and graphene foam nanoarchitectures may address the intractable pulverization problem of Si electrode.